¿Cómo se posiciona la comunicación digital en Independiente del Valle? (Monográfico) - Campos Bastidas, Pablo Rodrigo (2024)
Independiente del Valle burst into Ecuadorian professional soccer in 2007 with a mission: to do things differently. Today, 16 years later, the team is a national and regional benchmark on how to manage a club from a business and disruptive perspective, in a complex and conventional industry such as football. “A different club” is the slogan used by the team in their messages on social networks. Through the following pages, the intention is to show how the Ecuadorian club adopted new paths and approaches to be different. Institutionally, in sports and in the ways of communicating and positioning itself as a brand.